Friday

April 18, 2014

April 18, 2014

Posted by **Help** on Thursday, September 10, 2009 at 11:25pm.

f(0)=

f(-1)=

f (2)=

- algebra -
**drwls**, Friday, September 11, 2009 at 7:10amPlug in x = 0 and compute f(x) using the formula given. In the first case:

3*0^2 - 5*0 = 0

Then do the same thing for x = -1 and x = 2.

**Related Questions**

algebra - find the indicated outputs for f(x)=3x^2-5x I get f(0)=0 f(-1) = 1 f(2...

Algebra - trouble with outputs.... Find the indecated outputs for f(x)=3x^2 - 5x...

Algebra - (Can someone please help?) Find the indicated outputs for f(x)=3x^2-5x...

Algebra - Find the indicated outputs for f(x)=¡¼5x¡½^(2 )-2x f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)= 4x^2- 5x= f(0)= f(-1)= f(2)=

algebra - find the indicated outputs for f(x)= 4x-5x= f(0)= f(-1)= f(2)=

Algebra 1 - Find the indicated outputs for f(x)=4x(2)-5x f(0)=? f(-1)=? (f(2)=?

Algebra - find the indicated outputs f(x)=2x^2-3x f(0)=? f(-1)=? f(2)=? help?

Math - Find the indicated outputs for f(x)= 5x^2-5x. F(0) = 0 f(-1)= 1 f(2)= 45 ...

Math - Find the indicated outputs for f(x)=5x^2-2x. f(0)= f(-1)= f(2)=